OPTIMALISASI PERAN ADMINISTRASI PUBLIK DALAM PROGRAM PENCEGAHAN STUNTING DI DESA KABINUANG, KECAMATAN DAMPAL UTARA - Taufik Riski; Nursifa Nursifa (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Madako Tolitoli, 2025)
Stunting remains a public health problem in Kabinuang Village, North Dampal District, influenced by weak coordination between village officials, suboptimal public administration management, and low community participation in health programs. These conditions have resulted in the suboptimal implementation of stunting prevention programs at the village level. This community service activity aims to assess and strengthen the role of village public administration in supporting the effectiveness of sustainable stunting prevention programs. The method used was participatory action research involving village officials, health cadres, and the community through training on administrative management and program planning, mentoring for the implementation of toddler nutrition programs, and participatory discussions with residents and relevant stakeholders. The results of the activity showed an increase in the understanding and capacity of village officials in administrative management and program planning, improved cross-sector coordination, and the formation of a more effective communication forum. Furthermore, community participation has increased, particularly in monitoring toddler nutritional status and supporting stunting prevention programs. The conclusion of this activity indicates that strengthening village public administration through a participatory approach can increase the effectiveness and sustainability of stunting prevention programs at the village level.